Effect of high dry solids loading on enzymatic hydrolysis of acid bisulfite pretreated Eastern redcedar - Ramachandriya, Karthikeyan D.; Wilkins, Mark; Atiyeh, Hasan K.; Dunford, Nurhan T.; Hiziroglu, Salim (Bioresource technology, 2013)
•Eastern redcedar was enzymatically hydrolyzed at 2–20% solids loading.•More than 100g/L fermentable glucose was achieved at 16% and 20% solids loading.•Addition of metal balls during hydrolysis helped overcome rheological challenges.•Separate high solids hydrolysis and fermentation produced 52g/L of ethanol.•An enzyme loading of 46FPU/g glucan was required to produce high glucose titers. This study investigates hydrolysis of cellulose from Eastern redcedar to glucose at high solids loading. Enzymatic hydrolysis of pretreated redcedar was performed with 0.5ml Accelerase® 1500/g glucan (46FPU/g glucan) using dry solids loading from 2% to 20% (w/w). Rheological challenges observed at high solids loading were overcome by adding stainless steel balls to shake flask reactors. The highest glucose concentration, 126g/L (84% glucan-to-glucose yield), was obtained using 20% solids loading with stainless steel balls as a mixing aid. This enzymatic hydrolyzate was fermented into ethanol using Saccharomyces cerevisiae D5A to produce 52g/L of ethanol (corresponding to 166L/dryMg of redcedar). Reducing enzyme dosage at 16% solids loading from 46 to 11.5FPU/g glucan reduced glucan-to-glucose yields. This study has demonstrated the possibility of extracting sugars from the invasive species of Eastern redcedar with high solid loadings and their conversion into ethanol.